A New High Throughput Sequencing Assay for Characterizing the Diversity of Natural Vibrio Communities and Its Application to a Pacific Oyster Mortality Event - King, William L.; Siboni, Nachshon; Kahlke, Tim; Green, Timothy J.; Labbate, Maurizio; Seymour, Justin R. (Frontiers in Microbiology, 2019)
The Vibrio genus is notable for including several pathogens of marine animals and humans, yet characterisation of Vibrio diversity using routine 16S rRNA sequencing methods is often constrained by poor resolution beyond the genus level. Here, a new high throughput sequencing approach targeting the heat shock protein (hsp60) as a phylogenetic marker was developed to more precisely discriminate members of the Vibrio genus in environmental samples. The utility of this new assay was tested using mock communities constructed from known dilutions of Vibrio isolates. Relative to standard and Vibrio-specific 16S rRNA sequencing assays, the hsp60 assay delivered high levels of fidelity with the mock community composition at the species level, including discrimination of species within the Vibrio harveyi clade. This assay was subsequently applied to characterise Vibrio community composition in seawater and delivered substantially improved taxonomic resolution of Vibrio species compared to 16S rRNA analysis. Finally, this assay was applied to examine patterns in the Vibrio community within oysters during a Pacific oyster mortality event. In these oysters, the hsp60 assay identified species-level Vibrio community shifts prior to disease onset, pinpointing V. harveyi as a putative pathogen. Given that shifts in the Vibrio community can precede, cause and follow disease onset in numerous marine organisms, there is a need for an accurate high throughput assay for defining Vibrio community composition in natural samples. This Vibrio-centric hsp60 sequencing assay offers the potential for precise high throughput characterisation of Vibrio diversity, providing an enhanced platform for dissecting Vibrio dynamics in the environment.